PELESTARIAN SENI BUDAYA DAN PERMAINAN TRADISIONAL MELALUI TEMA KEARIFAN LOKAL DALAM KURIKULUM PENDIDIKAN ANAK USIA DINI - Betty Yulia Wulansari (Universitas Muhammadiyah Ponorogo, 2017)
Indonesia is a country rich traditional art and culture danpermainan. Cultural arts and traditional games are so diverse but many are endangered because there is nothing to preserve it. The longer, the Indonesian nation many know the game only through the written documentation. This is exacerbated by the current digital game technology that began to mushroom, and the change of social system in a more individualistic society. Thus it takes effort to keep preserve traditional games through the Early Childhood Education (ECD). ECD is an institution that supports the social system of friends to play traditional games. Curriculum development by adding themes Local Wisdom can be performed on all early childhood institutions in Indonesia so that our country is not experiencing a crisis of extinction of traditional games.